2006
DOI: 10.1385/endo:30:2:217
|View full text |Cite
|
Sign up to set email alerts
|

Globular Adiponectin Augments Insulin Secretion from Pancreatic Islet β Cells at High Glucose Concentrations

Abstract: Adiponectin plays an important role in improving insulin resistance and preventing atherosclerosis. However it has been rarely reported that adiponectin influences insulin secretion because its receptor was identified in human islet beta cells. In order to investigate the direct effect of adiponectin on pancreatic islet beta cells, we performed an insulin secretion test in purified rat islets, which were incubated with adiponectin (100 ng/mL) at low (3.3 mM) and high (16.7 mM) glucose concentrations. Furthermo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
40
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 32 publications
4
40
0
2
Order By: Relevance
“…Finally, our results are concurrent with previous reports that suggest predominant expression of AdipoR1 in pancreatic islets (14). However, knockdown or overexpression of AdipoRs in pancreatic beta cells did not affect adiponectin-induced changes in Akt or ERK phosphorylation or cleaved caspase-3.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Finally, our results are concurrent with previous reports that suggest predominant expression of AdipoR1 in pancreatic islets (14). However, knockdown or overexpression of AdipoRs in pancreatic beta cells did not affect adiponectin-induced changes in Akt or ERK phosphorylation or cleaved caspase-3.…”
Section: Discussionsupporting
confidence: 92%
“…The impact of adiponectin on insulin secretion in vitro has so far been variable in literature. Upon stimulation with adiponectin, no effect was observed in basal or GSIS from human islets; basal secretion was reduced, whereas GSIS was increased in insulin-resistant mice; GSIS was increased in isolated rat islets; and basal and GSIS was increased during sustained glucotoxicity, and fatty acid-induced inhibition of GSIS was reversed in cultured beta cells (14,16,21,22,29). Therefore, with the human islet study as an exception, there appears to be a general trend for adiponectin to increase GSIS, especially under stressed conditions, such as in insulin resistance, lipotoxicity, glucotoxicity, or serum starvation.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Of interest, leptin stimulates AMPK activity in skeletal muscle (Minokoshi and Kahn, 2003), expressing predominantly the 2 subunit, but neither this adipokine (Leclerc et al, 2004c) nor adiponectin (Okamoto et al, 2008) (GAR, Wheeler, MB unpublished results) was reported to have any effect on AMPK activity in primary β-cells. However, and in contradictory findings, others have reported the activation of AMPK by adiponectin in MIN6 cells (Huypens et al, 2005) and in rat islets (Gu et al, 2006).…”
Section: Ampk Isoform Expression In β-Cellsmentioning
confidence: 97%
“…The studies exploring AdipoR1 and AdipoR2 expression demonstrated that they are fairly ubiquitously expressed with high levels in metabolically active tissues such as skeletal muscle 48,76,77 liver 48,77,78 , heart [79][80][81] and adipose tissue 82,83 . They are also expressed in other adiponectin responsive cells and tissues such as osteoblasts 84 , pancreas 85,86 , leukocytes 75,87 and the brain 88 .…”
Section: Adiponectin Receptor Expression and Regulationmentioning
confidence: 99%